The chiropractic profession in Denmark 2010-2014: a descriptive report. - Nielsen, Orla Lund; Kongsted, Alice; Wulff Christensen, Henrik (Chiropractic & Manual Therapies, 2015)
Background: The chiropractic profession has been well established in Denmark for several decades with state authorization, partial reimbursement by the state and a formal academic education. Biennial systematic data collections among all chiropractors and clinics have been performed since 2010 in order to provide exact information on the profession to The Danish Chiropractic Association (DCA). It is the aim of this study to outline the major characteristics and developments of the chiropractic profession in Denmark to make this information accessible to other stakeholders, domestic as well as foreign. Methods: Using contact information from the DCA, two questionnaires were distributed electronically to all individual members of the association actively working as chiropractors and all clinics respectively in 2010, 2012 and 2014. The questions asked were developed for this specific survey. Results: Response rates varied between 59 and 78 % for the clinic questionnaires and 75 to 86 % for the individual questionnaires. Almost half the Danish chiropractors were educated in Denmark and a small majority was female. The average Danish chiropractor of 2014 was 44 years old, graduated 17 years earlier, and worked full time in a primary care clinic with at least one colleague. Half the chiropractors spent more than 20 h a year on continued professional development. Danish chiropractic clinics had a median of 3 treatment rooms, most had digital X-ray equipment, around 6 out of 10 had exercise facilities, and 1 out of 4 employed a physiotherapist. Three out of 4 clinics employed a secretary, too. The average duration of a consultation was 40 min for a new patient and 13 min for a follow-up consultation. Virtually all Danish chiropractors working in the primary sector made use of manipulation as one of their treatment modalities. Conclusion: This is the first study to describe the state and latest development of the chiropractic profession in Denmark using repeated surveys. Displaying various characteristics of both clinics and individual chiropractors, the image emerging is one of a stable profession where rapid or drastic changes are not taking place over short intervals of time.